Adding Inverter Fault Detection to Model-Based Predictive Control for Flying-Capacitor Inverters - Druant, Joachim; Vyncke, Thomas; De Belie, Frederik; Sergeant, Peter; Melkebeek, Jan (IEEE transactions on industrial electronics (1982), 2015)
As inverters are often used in critical applications, reliability is an important issue. In particular, the power electronic switches and gate drivers, the most essential components of the inverter, are vulnerable parts in real live operation. Therefore, this paper focuses on open-switch fault detection for multilevel inverters. When a single-switch open-circuit fault occurs in one of the power electronic switches, the algorithm can detect the fault and the switch that is causing it. The detection is worked out for both a linear resistive inductive load and an induction motor. The proposed algorithm is an extension of an already available finite-set model-based predictive control algorithm. Therefore, no extra hardware or measurements are required. This paper also discusses a suggested method for reconfiguration after fault detection. Computer simulation and experimental verifications validate the proposed methods.